CRISIS OF SOCIAL INFRASTRUCTURE IN RURAL AREAS OF UZBEKISTAN DURING TOTALITARIAN REGIME IN 1965-1985 - Nasyrov, Rashod (International Journal of Psychosocial Rehabilitation, 2020)
The article aims to clarify the crisis of social policy in rural areas of Uzbekistan caused by completely inappropriate functioning of the administrative-centralist system, firmly established in the agricultural sector and completely incompatible with the objectives of laws and development. It also compares and contrasts the degree of social infrastructure development and the effectiveness of social policies of Uzbekistan and other Soviet Union Republics2. The main methods employed in this study are objectivity, historicism together with compare and contrast analysis.The results show that the lack of coordination and departmental unity was the main reason for rural underdevelopment compared with other Soviet Republics.